ROLE OF SONOURETHROGRAPHY IN EVALUATION OF ANTERIOR URETHRAL STRICTURE AND ITS COMPARISON WITH RETROGRADE URETHROGRAPHY - Khan, Muhammad Babar; ahmood, Rashid M; Ghaffar, Abdul; Mahmood, Tariq (Pakistan Armed Forces Medical Journal, 2006)
Objective:  The aim of this study was to compare retro grade urethrography (RUG) and sonourethrography (SUG) for assessment of urethral strictures and to evaluate whether RUG underestimates stricture length, as has been reported.Study design:  Quasiexperimental study.Place and Time of Study:  The study was performed in the department of Radiology PNS Shifa Karachi from January 2004 till December 2004.Patients and Methods: Forty male patients diagnosed with anterior urethral stricture were assessed for presence of strictures and their length by conventional contrast urethrography and sonourethrography. Contrast urethrography was carried out by retrograde injection of Urograffin 76% under fluoroscopic guidance. Sonourethrography was done with a 7.5 MHz small parts transducer. Stricture lengths were recorded and compared. Results:  Analysis of the results showed that the estimation of stricture length measured by contrast urethrography was under-estimated as compared to sonourethrography. The difference between the two tests was significant (P < 0.001) and the correlation coefficient was poor (r = 0.493). When the strictures were grouped into penile and bulbar anatomical locations the results remained highly significant in the bulbar region (P = 0.0001) however no significant difference was found in the estimated length for penile strictures (P = 0.25).Conclusion:  Sonourethrography is a good adjunct investigation before definitive surgical therapy particularly in the bulbar region where conventional contrast urethrography was shown to underestimate stricture length significantly.